Lectin Based Hemagglutination Assay: A Screening Test For Thyroid Disorders - DHIRAJ TRIVEDI; CHHAYA TRIVEDI; PRAMOD KAMBLE; MC CHANDRU (International Journal of Pharma and Bio Sciences, 2011)
The Present study demonstrates the diagnostic characteristics of Pedilanthus tithymoloides, agglutinin (PTA), lectin based hemagglutination method for screening of thyroid disorders as compared with RIA as gold standard. The result estimates 90% sensitivity, 95.55% specificity and 92.63% observed agreement with RIA test in thyroid disorders. The result of hyperthyroidism, hypothyroidism and cretinism are discussed and these results project Lectin based hemagglutination as simple, reliable, cost effective and an alternative method of choice for screening of thyroid disorders.